LINC00665 Induces Acquired Resistance to Gefitinib through Recruiting EZH2 and Activating PI3K/AKT Pathway in NSCLC - Xinyin Liu; Xiyi Lu; Fuxi Zhen; Shidai Jin; Tongfu Yu; Quan Zhu; Wei Wang; Kun Xu; Jiaqi Yao; Renhua Guo (Elsevier, 2019)
Gefitinib, a tyrosine kinase inhibitor of epidermal growth factor receptor, has been used as the first choice of treatment for advanced non-small-cell lung cancer. However, during the course of treatment, cancer cells often develop resistance to gefitinib without fully understood mechanisms. In this study, we aimed to elucidate an important role of long intergenic non-coding RNA 00665 in developing resistance to gefitinib in non-small-cell lung cancer. We showed that long intergenic non-coding RNA 00665 expression was significantly upregulated in lung cancer tissues and cells with acquired gefitinib resistance. Long intergenic non-coding RNA 00665 knockdown restored gefitinib sensitivity both in vitro and in vivo by suppressing cell proliferation and inducing apoptosis. Moreover, knockdown of long intergenic non-coding RNA 00665 markedly reduced activation of EGFR and its downstream event protein kinase B (AKT). Moreover, LINC00665 could interact with EZH2 and regulate the phosphatidylinositol 3-kinase (PI3K)/AKT pathway. Thus, our study suggests that long intergenic non-coding RNA 00665 is important for non-small-cell lung cancer to develop drug resistance and might be a potential biomarker for drug resistance and a therapeutic target for non-small-cell lung cancer. Keywords: lncRNA, LINC00665, acquired resistance, EGFR-TKIs, NSCLC